Cause and effect of calving difficulty in first calf heifers on subsequent reproductive performance and weaning weights of progeny - R.P. Bolze; R.J. Pruitt; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1983)
Eight years of records for 1495 2-year old beef heifer calvings from two Kansas ranches were analyzed to determine the cause and effect"¢ of calving difficulty on subsequent reproductive performance and weaning weights of progeny. The study involved two herds of Simmental cattle (spring and fall calving) and one herd of fall calving Angus cattle. Heifers were classified as either requiring or not requiring assistance with their first calf. Herds were analyzed separately. Percentages of heifers requiring assistance for the Angus, spring calving Simmental and fall calving Simmental herds were 36%, 57% and 38%, respectively. In all herds, calves from 2-year-old heifers requiring assistance were 5.5 to 10.3 lbs heavier at birth and had a 4.5 to 10% higher mortality rate than calves from unassisted heifers. Overall conception during a subsequent 63 day breeding season after their first calf was 9% lower for assisted than unassisted heifers. Angus heifers requiring assistance were 8 days younger at their first parturition. Spring calving Simmental heifers requiring assistance delivered 15% fewer calves within the first 21 days of the subsequent calving season. Calves from fall calving Simmental heifers requiring assistance weaned (unadjusted) 18 lb heavier. Nineteen percent more heifers requiring assistance with their first calf also had required assistance during their own birth. Maternal grand sires had a significant effect upon their daughters' reproductive and growth performance and upon their daughters' progeny performance.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Reproductive performance; Weaning weights; Growth; Calving difficulty